Thomas Merton: The true self and the quest for justice - Rakoczy, Susan (HTS teologiese studies, 2016)
The year 2015 marked the 100th anniversary of the birth of Thomas Merton who was born on31 January 1915. His writings cover diverse themes, which are of value to a myriad of faithtraditions. This article will trace his understanding of holiness and the way in which Mertonemphasised participation in the transformation of the world. It commences with a biographicaloverview of Merton and then Merton’s understanding of ‘holiness’ as growth of the ‘true self’in God is discussed. His work as social critic is outlined and the article ends with a reflectionof Merton’s understanding of ‘love’ and ‘compassion’ – a life before God.